Disabling proximal-distal quadriparesis as initial symptom of dermatomyositis: a case report - Vences, Miguel Angel (2025)
Dermatomyositis is considered a rare disease that affects the quality of life of patients. Herein, we described the case of a 48-year-old man with initial neuromuscular symptoms of disabling proximal-distal quadriparesis. He had an antinuclear antibody speckled pattern and elevated levels of creatine kinase and transaminases. Muscle magnetic resonance imaging revealed muscle edema and fatty atrophy in the pelvic girdle and shoulder girdle muscles. Electromyography showed signs of abundant denervation—predominantly proximal muscles and small-amplitude polyphasic motor units. Muscle biopsy revealed perivascular inflammation and perifascicular atrophy, CD3- and CD4-positivity, with CD8-positivity to a lesser extent than CD4 positivity, and CD20-negativity. He received induction treatment with methylprednisolone and cyclophosphamide and maintenance treatment with prednisone and azathioprine. He showed favorable progress at 1 year of follow-up, exhibiting adequate muscle strength and functional independence. Thus, this presentation and the associated systemic manifestations should be considered for timely management and improvement of the functional prognosis of patients.